A Terminal Iron Nitrilimine Complex: Accessing the Terminal Nitride through Diazo N−N Bond Cleavage - Aghazada, Sadig; Miehlich, Matthias; Messelberger, Julian; Heinemann, Frank Wilhelm; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2019)
A novel method for the N−N bond cleavage of trimethylsilyl diazomethane is reported for the synthesis of terminal nitride complexes. The lithium salt of trimethylsilyl diazomethane was used to generate a rare terminal nitrilimine transition metal complex with partially occupied d-orbitals. This iron complex 2 was characterized by CHN combustion analysis, 1H and 13C NMR spectroscopic analysis, single-crystal X-ray crystallography, SQUID magnetometry, 57Fe Mössbauer spectroscopy, and computational analysis. The combined results suggest a high-spin d 6 (S=2) electronic configuration and an allenic structure of the nitrilimine ligand. Reduction of 2 results in release of the nitrilimine ligand and formation of the iron(I) complex 3, which was characterized by CHN combustion analysis, 1H NMR spectroscopic analysis, and single-crystal X-ray crystallography. Treatment of 2 with fluoride salts quantitatively yields the diamagnetic FeIV nitride complex 4, with concomitant formation of cyanide and trimethylsilyl fluoride through N−N bond cleavage.
CRIS-Team Scopus Importer:2019-11-15
Keywords: diazo compounds; iron; N-heterocyclic carbenes; N−N activation; terminal nitrides